Optimization of Waste Banks in Schools: Education-Based Solutions to Overcome Environmental Pollution - Dewi Indah Pratiwi; Asramid Yasin (AL-ISHLAH: Jurnal Pendidikan, 2022)
Education, especially character education, is related to the development of human morality and spirituality from an environmental perspective. This understanding of waste management is related to the character of caring for the environment based on various existing character values. One way of managing waste in schools is by establishing a waste bank. Therefore, this study aims to explain the optimization of waste banks in schools as an effort to overcome environmental pollution through education. This study took the research location at the Adiwiyata school in the Subang Regency. This research uses a qualitative approach. The researchers used observations, documentation, and interviews with students, teachers, employees, and school residents. Data analysis and research results are presented descriptively using the Miles Huberman model. The study results show that education-based solutions in overcoming pollution and protecting the environment through optimizing the waste bank at Adiwiyata elementary school run effectively and can be one of the means of environmental care education. This is evidenced by the active participation of all relevant parties in the school in the implementation of the waste bank program, which includes students, teachers, employees, and other school residents.